2020
DOI: 10.1155/2020/5273914
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism of the Effect of Huanglian Jiedu Decoction on Type 2 Diabetes Mellitus Based on Network Pharmacology and Molecular Docking

Abstract: Background. Huanglian Jiedu Decoction (HLJDD) is a Traditional Chinese Medicine (TCM) formula comprising four herbal medicines. This decoction has long been used in China for clinically treating T2DM. However, the molecular mechanism of HLJDD treat for T2DM is still not fully known. Hence, this study was designed to reveal the synergistic mechanism of HLJDD formula in the treatment of T2DM by using network pharmacology method and molecular docking. Methods. Retrieving and screening of active components of diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 36 publications
2
27
0
Order By: Relevance
“…Another study have shown that AKT1 is an important pathogenic target in T2DM. Lipopolysaccharide induced production of VEGF in whole blood cultures, and increases signi cantly in T2DM (Yin et al 2020). It acts as a semiselective barrier and the structural integrity of vascular endothelium is essential for the maintenance of vascular homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Another study have shown that AKT1 is an important pathogenic target in T2DM. Lipopolysaccharide induced production of VEGF in whole blood cultures, and increases signi cantly in T2DM (Yin et al 2020). It acts as a semiselective barrier and the structural integrity of vascular endothelium is essential for the maintenance of vascular homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Docking studies were conducted between celastrol and key targets using Autodock 4.2. The structure modification process included ligand and water removal, hydrogen addition, amino acid optimization, and patching ( Pradeepkiran et al, 2015 ; Yin et al, 2020 ; Li et al, 2021 ; Venkataramaiah et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The degree of freedom was indicated by node size and color. The topological properties of the target genes were analyzed using the CytoNCA tool (Cytoscape software plugin) ( Tang et al, 2015 ; Bei Yin et al, 2020 ). The PPI network was used to screen key targets of the new treatment based on a degree centrality (DC) > two-fold of the median and betweenness centrality (BC), closeness centrality (CC), and an eigenvector centrality (EC) > one-fold of the median.…”
Section: Methodsmentioning
confidence: 99%